Tales of Tristoria: Exploring Finding Meaning of Life Through Acceptance of Death - Jeremi Noverian; Dwi Setiawan (Kata Kita: Journal of Language, Literature, and Teaching, 2021)
Humanity has their own meanings of life. Those meanings are meant to guide them towards fulfillment. People have different triggers that propel them to find their meanings of life, for example death anxiety. This novel project follows Trista, the bearer of a Curse which has the power to kill her if she uses it. As a result, she fears death and struggles to find her meaning of life, because she feels sorrow caused by her death anxiety. To better explore the issue, I apply Paul Wong’s Meaning Management Theory about meaning of life and death anxiety in the story. I find that death anxiety makes someone like Trista experience a life-changing experience to motivate her to find meaning, and the death anxiety subsides when a person finds meaning, accepts, and no longer fears death. A person who finds meaning will live life to the fullest based on their meanings. Keywords: Meaning of life, death anxiety, death acceptance